Utilization of the Business Process Maturity Model as a Proposed Architectural Planning of Business Model Concept - Sawali Wahyu; Husni S. Sastramihardja (Faculty of Computer Science Universitas Indonesia, 2020)
This research is a part of previous research which succeeded in producing business model architecture planning, the purpose of this research is to develop previous research using business model maturity measurement methods as a proposed business model architecture planning concept. By taking the same case study theme as Tiara Payung Putra (TPP) company. TPP is known as a distributor company in cooperation with Pertamina's (Bulk LPG Filling and Filling Station). TPP's main business activity is to distribute goods in the form of LPG to 76 bases spread across the Balaraja district. The current condition of the business model architecture illustrates the business activities that exist in the TPP. The main problems that occur in the TPP are not integrated the external system with internal business activities in the company, and the lack of IT resource support. For this reason, the Business Process Maturity Model is needed as a benchmark, which can be proposed as a business architecture planning concept. Support for the Enterprise Architecture Planning (EAP) Framework method focuses on the business model architecture domain. The architecture of the business model illustrates how TPP carries out business activities and functions to achieve its objectives. The results of this study produce proposed business model architecture planning concepts in the form of Business Model Maturity Level Measurement, SI / IT architecture concepts, and Business Architecture Planning roadmap, which are beneficial for Tiara Payung Putra (TPP) company for business model architecture planning.